Establishing patterns in the stressed-strained state of concrete sleepers with prestressed composite reinforcement and their models - Plugin, Andrii; Murygin, Maxim; Plugin, Dmytro; Najafov, Elshad; Musiienko, Serhii; Lobiak, Oleksii (Eastern-European Journal of Enterprise Technologies, 2025)
This study investigates the finite-element and physical models of railroad sleepers made of concrete with steel and composite prestressed reinforcement. Reinforced concrete sleepers withstand mechanical loads well but have low electrical resistance, which contributes to traction current losses, leakage currents and electrocorrosion of linear structures on electrified railroads, as well as disruption of auto-lock. Since low electrical resistance is due to the electrical conductivity of steel reinforcement, its replacement with composite makes it possible to solve a number of problems in railroad operation. However, its use for sleepers is complicated by the difference from steel reinforcement in elasticity and remains insufficiently studied. Sleeper models and a scheme for their testing have been devised, which corresponds to the standard sleeper test. Calculation and full-scale experiments with loading the models have been performed. It has been established that as the models are loaded and the deformation moment increases, it evolves in three stages: crack formation; their development to the formation of a plastic hinge; failure with reinforcement slipping. In the model with composite reinforcement, compared to steel reinforcement, the moments corresponding to these stages are smaller by values that correlate with lower tension forces and the modulus of elasticity of the reinforcement. The type of reinforcement affects all moments characterizing the strength and crack resistance of the models less than the pre-tensioning forces. The results from the calculated and full-scale experiments have been compared. Correction factors were proposed for calculating the moments of crack formation in sleepers. The results make it possible to design sleepers with composite reinforcement of the required crack resistance. Such sleepers could be implemented provided that a positive result is obtained from their experimental operation on an electrified section of the railroad